2022
DOI: 10.3389/fmed.2022.919502
|View full text |Cite
|
Sign up to set email alerts
|

Appendicular Skeletal Muscle Index and HbA1c Evaluate Liver Steatosis in Patients With Metabolic Associated Fatty Liver Disease

Abstract: Background and Aim(s)Liver steatosis, as the main feature of metabolic associated fatty liver disease (MAFLD), was associated with the progression of liver fibrosis and metabolic syndrome, which needed to be estimated accurately. In this study, we explored the significance of appendicular skeletal muscle index (ASMI) in evaluating liver steatosis of MAFLD patients.MethodsEight hundred and ninety-nine cases with MAFLD from 2017 to 2018 National Health and Nutrition Examination Surveys (NHANES) database were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… 18 By altering the metabolism of fat muscles and IR, loss of muscle mass and obesity primarily encourage lipotoxic effects and have a negative impact on NAFLD onset and progression. 19 Sarcopenia and obesity increase the risk of NAFLD 20 and all-cause mortality compared to obesity alone. 21 In the present study, the NAFLD group had greater BMI and VFA and lower ASMI and LSMI than the non-NAFLD group.…”
Section: Discussionmentioning
confidence: 99%
“… 18 By altering the metabolism of fat muscles and IR, loss of muscle mass and obesity primarily encourage lipotoxic effects and have a negative impact on NAFLD onset and progression. 19 Sarcopenia and obesity increase the risk of NAFLD 20 and all-cause mortality compared to obesity alone. 21 In the present study, the NAFLD group had greater BMI and VFA and lower ASMI and LSMI than the non-NAFLD group.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the ASMI measure was computed through dividing ASM by the height squared, as indicated by the formula: ASMI = ASM/height 2 . [ 18 ]…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the ASMI measure was computed through dividing ASM by the height squared, as indicated by the formula: ASMI = ASM/height 2 . [18] For this investigation, we employed total bone mineral density as the outcome variable. Qualified radiology technologists employed DXA to determine BMD.…”
Section: Exposure and Outcome Variablementioning
confidence: 99%
“…A Korean report on MAFLD and muscle mass showed that MAFLD and a loss of skeletal muscle mass were closely correlated, with diabetes-associated MAFLD being associated with the greatest loss of skeletal muscle mass, and patients with advanced liver fibrosis had a significantly higher rate of loss of skeletal muscle mass than those without the advanced disease [43]. Combining appendicular skeletal muscle mass and diabetes can also predict the degree of hepatic steatosis in MAFLD [44]. IR and body fat mass are significantly interrelated in MAFLD patients [45].…”
Section: Boby Composition In Fatty Livermentioning
confidence: 99%